2022
DOI: 10.1021/acs.jpcc.2c06055
|View full text |Cite
|
Sign up to set email alerts
|

Impact Electrochemistry of MoS2: Electrocatalysis and Hydrogen Generation at Low Overpotentials

Abstract: MoS2 materials have been extensively studied as hydrogen evolution reaction (HER) catalysts. In this study nanoparticulate MoS2 is explored as a HER catalyst through impact voltammetry. The onset potential was found to be −0.10 V (vs RHE) at pH 2, which was confirmed to be due to HER by scale-up of the impact experiment to generate and collect a sufficient volume of the gas to enable its identification as hydrogen via gas chromatography. This is in contrast to electrodeposited MoS2, which was found to be stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 61 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…MoS 2 is one of the most studied transition metal dichalogenides (TMD) due to its potential in both semiconductor devices and electrochemical devices . MoS 2 in the context of fuel cell applications has been used to facilitate the oxygen reduction reaction (ORR) and as a hydrogen evolution catalyst (HER) for electrolyzers. However, it has not been explored for crossover mitigation, as it has been suggested that proton conduction through exfoliated MoS 2 flakes is not substantial .…”
Section: Resultsmentioning
confidence: 99%
“…MoS 2 is one of the most studied transition metal dichalogenides (TMD) due to its potential in both semiconductor devices and electrochemical devices . MoS 2 in the context of fuel cell applications has been used to facilitate the oxygen reduction reaction (ORR) and as a hydrogen evolution catalyst (HER) for electrolyzers. However, it has not been explored for crossover mitigation, as it has been suggested that proton conduction through exfoliated MoS 2 flakes is not substantial .…”
Section: Resultsmentioning
confidence: 99%